Automatic Generation of Finite Difference Field Solvers for Toroidally Confined Plasmas (Communications in Computational Physics, 2020)
Flux coordinates and field-line coordinates are ubiquitous in magneticallyconfined plasma research. Most of these coordinates are essentially non-orthogonalcurvilinear coordinates, in which the differential operators are rather complicated.This article reports an automatic tool, OpGen, for generating a finite difference coefficient matrix for field solvers by using a computer symbolic computation system.This tool is suitable for, but is not limited to, code development for toroidally confinedplasmas.